Early Experience with Laparoscopic Inguinal Hernia Repair - SHAHIDULLAH AHMAD, VIQAR ASLAM, NAEEM MUMTAZ, WAQAR ALAM JAN, (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate our experience with Laparoscopic hernia repair with regards to, complications,time to full recovery, return to work, and recurrence. Methodology: This was a descriptive prospective study, performed in the Surgical B Unit of Lady Reading Hospital, Peshawar from 1st January, 2011 to 1st November 2011. Patients were admitted from the out-patient department. Exclusion criteria included-obstructed/strangulated hernia, patients with previous pelvic surgery, patients not fit for general anaesthesia and children. After written informed consent, either a TEP or TAPP repair was done under general anaesthesia. The course of the procedure was noted for any intraoperative complications, total operating time and conversion to open procedure. Any complications in the post-operative period were also noted. Follow-up was done at 1 week, one month, 4 month and 6 month intervals and any long term complications noted. Results: A total of 44 patients were included in the study. Male to female ratio was 10:1. Mean age was 37.5 years. Thirty six patients presented with primary hernia while 8 patients had recurrent hernia.In 20 patients, hernia was on the right side while in 16 patients it was on the left side. Eight patients had bilateral hernia. Indirect hernia was seen in 25 patients and direct hernia was present in 14 cases. TEP procedure was done in 8 patients while TAPP procedure was carried out in 36 patients. Major complications encountered were: conversion to open procedure in 4 patients, excessive bleeding in 2 patients, surgical emphysema in 3 patients, significant post-operative pain in 6 patients and port site infection in 2 cases. No recurrence was seen at the end of study. Conclusion: Laparoscopic inguinal hernia repair can be a routine procedure with results comparable to those of open procedures.It is well suited for recurrences. The visualization of structures is clear and leads to a defect-specific closure.